Fossil pollen indicates an explosive radiation of basal Asteracean lineages and allied families during Oligocene and Miocene times in the Southern Hemisphere - Barreda, Viviana Dora; Palazzesi, Luis; Tellería, María Cristina; Katinas, Liliana; Crisci, Jorge Victor (Review of Palaeobotany and Palynology)
Much of our knowledge of the past distribution and radiation of Asteraceae and allied families depends on the fossil pollen record. In recent years, new discoveries are coming to light from southern Africa, Australia, New Zealand, and southern South America (Patagonia). Unequivocally assigned morphotaxa from accurately dated sediments have permitted for the first time a comprehensive review of the past distribution of the most important core of the sunflower alliance of families (Menyanthaceae, Goodeniaceae, Calyceraceae and Asteraceae). The main goal of this contribution is to explore the major evolutionary radiation of the basal lineages of Asteraceae (Mutisioideae and Barnadesioideae) and allied relatives (Menyanthaceae, Goodeniaceae and Calyceraceae) on the basis of the worldwide fossil pollen records. Several taxa, which today are restricted to isolated geographic regions, were widespread in the Southern Hemisphere during Paleogene times. Menyanthaceae, Goodeniaceae and Mutisioideae (Asteraceae), for example, had a wide distribution over Gondwanan landmasses in the Oligocene and are now drastically reduced in their geographic range. Early Neogene records, in contrast, suggest extinction and diversification events that progressively led to the present day configuration. In broad terms, the distribution of Miocene fossils assigned to this clade (Barnadesioideae, Nassauvieae, and Calyceraceae) agrees with that of their present distribution. The major floristic turnovers coincided with the final isolation of Antarctica, leading to cooler, drier, and more seasonal climates and forced the evolution and distribution of these Gondwanan elements. Fil: Barreda, Viviana Dora. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales “Bernardino Rivadavia”; Argentina Fil: Palazzesi, Luis. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo ...